Modeling How to Grow: An Inductive Examination of Humble Leader Behaviors, Contingencies, and Outcomes - Owens, Bradley P.; Hekman, David R. (Academy of Management Journal, 2012)
Although a growing number of leadership writers argue leader humility is important to organizational effectiveness, little is known about the construct, why some leaders behave more humbly than others, what these behaviors lead to, or what factors moderate the effectiveness of these behaviors. Drawing from 55 in-depth interviews with leaders from a wide variety of contexts, we develop a model of the behaviors, outcomes, and contingencies of humble leadership. We uncover that leader humility involves leaders modeling to followers how to grow and produces positive organizational outcomes by leading followers to believe that their own developmental journeys and feelings of uncertainty are legitimate in the workplace. We discuss how the emergent humility in leadership model informs a broad range of leadership issues, including organizational development and change, the evolution of leader-follower relationships, new pathways for engaging followers, and integrating top-down and bottom-up organizing.